Women's Perceptions of Postpartum Weight Retention and their Body Image in Relation to Breastfeeding Outcomes in Japan - Inoue, Madoka; Binns, Colin (Nova Science Publishers, 2013)
Weight retention in the postpartum period is a concern for many women following the increase in weight during pregnancy and they often struggle to return to pro-pregnancy levels. Postpartum weight retention may lead to obesity that is then associated with increased rates of several chronic diseases, including type 2 diabetes and cardiovascular disease. Prolonged breastfeeding is believed to help with weight loss during the postpartum period. Breastfeeding and in particular, ‘exclusive breastfeeding' for the first six month of life, provides a wide range of health benefits for infants but also to mothers. Most pediatric organizations recommend exclusive breastfeeding for six months and then continuing for as long as the mother desires. In Japan, women's body image has a strong influence on control of their weight due to the prevailing cultural norm that ‘being slim is beautiful'. This is an important factor when considering postpartum weight retention together with breastfeeding practices. Japan has the least number of women who are overweight among all of the developed countries. But despite this many Japanese women perceive themselves to be overweight both before and after pregnancy. While they of necessity increase their weight during pregnancy many undertake activities to regain pro-pregnancy body shape soon after birth due to their desire to regain their ideal body image of being slim. A study of Japanese postpartum women residing in Himeji-city, (n = 1,612) showed that more than 42% of women believed that they had not yet returned to their weight at 18 months postpartum, even though 18% were actually in the ‘underweight range (Body Mass Index ≤ 18.5)'. The women who had returned to their pro-pregnancy weight stated that their weight loss usually occurred within six months after birth (59.6%), during the time when most were breastfeeding.ln the study, the postpartum women were asked about their level of concern about body appearance using the Attention to Body Shape Scale (ABS). The average score of the ABS was 24.2 (Standard Deviation [SD] = 4.2) suggesting that postpartum women in Japan were highly conscious about their body shape. Women' body image is related to infant feeding practices as breastfeeding is associated with weight loss, but also breastfeeding may be associated with breast shape changes and hence changes in body image. In this chapter, we describe and discuss women's perceptions of postpartum weight retention and their body image in relation to breastfeeding outcomes, particularly focusing on a trend in Japan.